Discovery of New Potent anti-MERS CoV Fusion Inhibitors - Kandeel, Mahmoud; Yamamoto, Mizuki; Park, Byoung Kwon; Al-Taher, Abdulla; Watanabe, Aya; Gohda, Jin; Kawaguchi, Yasushi; Oh-hashi, Kentaro; Kwon, Hyung-Joo; Inoue, Jun-ichiro (Frontiers in Pharmacology, 2021)
Middle East respiratory syndrome coronavirus (MERS-CoV), capable of zoonotic transmission, has been associated with emerging viral pneumonia in humans. In this study, a set of highly potent peptides were designed to prevent MERS-CoV fusion through competition with heptad repeat domain 2 (HR2) at its HR1 binding site. We designed eleven peptides with stronger estimated HR1 binding affinities than the wild-type peptide to prevent viral fusion with the cell membrane. Eight peptides showed strong inhibition of spike-mediated MERS-CoV cell-cell fusion with IC50 values in the nanomolar range (0.25–2.3 µM). Peptides #4–6 inhibited 95–98.3% of MERS-CoV plaque formation. Notably, peptide 4 showed strong inhibition of MERS-CoV plaques formation with EC50 = 0.302 µM. All peptides demonstrated safe profiles without cytotoxicity up to a concentration of 10 µM, and this cellular safety, combined with their anti-MERS-CoV antiviral activity, indicate all peptides can be regarded as potential promising antiviral agents.